The Effect of Current Ratio, Return on Equity, And Company Size on Company Value in The Pharmaceutical Sector - Putri, Ika Swasti; Octavia, Ayu Nurafni; Fitriani, Laili Nur; Bulqis, Tiara (Economics and Business Solutions Journal, 2023)
ABSTRACTThis study aims to determine the effect of the current ratio, return on equity, and firm size on firm value. The population of this study is pharmaceutical sub-sector companies listed on the IDX for the 2017-2021 period. Samples taken using the purposive sampling method resulted in 8 companies and 40 data. The analytical model used in this study is a multiple linear regression model. Data processing and analysis using multiple linear regression analysis using the SPSS version 25 application. The results of this study found that the current ratio, return on equity, and company size did not have a significant effect on firm value in pharmaceutical sub-sector companies listed on the IDX in 2017-2021.  Keywords: Current Ratio; Return On Equity; Firm Size; Firm Value;